Traditional Sociocultural Values and the Society Interaction Model - Alaverdyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The model of traditional sociocultural values and the society interaction is discussed in the article. Sociocultural values provide feedback interaction with the society and, as a result, the central cultural circuit implements accumulating, saving, reproducing, handing over and programming functions of values. Social systems exist thanks to new sociocultural values that provide existence and development of the society.